2007
DOI: 10.1152/ajplung.00157.2005
|View full text |Cite
|
Sign up to set email alerts
|

Immunological determinants of ventilatory changes induced in mice by dermal sensitization and respiratory challenge with toluene diisocyanate

Abstract: The objective of the study was to characterize better the immunologic mechanisms underlying a previously developed animal model of chemical-induced asthma. BALB/c and severe combined immunodeficiency disease (SCID) mice received toluene diisocyanate (TDI) or vehicle on each ear on day 1 and/or day 7. On day 10, they were intranasally challenged with TDI or vehicle. Ventilatory function was monitored by whole body plethysmography for 40 min after challenge. Reactivity to methacholine was measured 23 h later: en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
63
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 69 publications
(76 citation statements)
references
References 21 publications
11
63
2
Order By: Relevance
“…It has been shown that dermal exposure leads to respiratory tract sensitization, and several groups have reported in mice that the magnitude of respiratory responses to inhaled isocyanates (an analogous low-molecular-weight chemical OA inducer) depends on prior frequency and concentration of dermal sensitization [30][31][32]. Relatedly, we found no statistical differences in IL-13 and IFN-g cytokine levels measured in the BALFs regardless of AP-mediated asthma induction.…”
Section: Figcontrasting
confidence: 52%
See 1 more Smart Citation
“…It has been shown that dermal exposure leads to respiratory tract sensitization, and several groups have reported in mice that the magnitude of respiratory responses to inhaled isocyanates (an analogous low-molecular-weight chemical OA inducer) depends on prior frequency and concentration of dermal sensitization [30][31][32]. Relatedly, we found no statistical differences in IL-13 and IFN-g cytokine levels measured in the BALFs regardless of AP-mediated asthma induction.…”
Section: Figcontrasting
confidence: 52%
“…However, this response was transient and did appear to compromise neither the health of the treated mice nor the therapeutic potential of hASCs. We and others have demonstrated the effectiveness of human ASC/MSC infusion within a xenogeneic environment in murine models of lung injury [13,17,24,27,30,41], although the present study highlights for the first time the development of a short host immune response against the infused xenogeneic cells. Nevertheless, from a clinical standpoint, the immunemediated clearance of allogeneic hASCs, particularly genetically engineered hASCs, in the treated lungs should reduce the safety concerns regarding the persistence of these implanted cells longer than required.…”
Section: Cd8mentioning
confidence: 59%
“…Using ELISA or mRNA expression techniques it has already been shown that cytokine production from cells of lymph nodes draining the site of chemical application for some chemicals shows specific profiles of synthesis that characterize processes of dermal or respiratory sensitization [8,27,28]. In our model, based on ELISA technique, we failed to show a specific profile of the cytokine production and found that both IL-4 as well as IFN-γ were increased after in vitro lymph node cell stimulation [42]. These analyses were confirmed in our present study and reported by other authors previously [17].…”
Section: Fig 5 Il-4 and Ifn-γ Gene Expression In Auricular Lymph Nomentioning
confidence: 76%
“…Studies in mice, rats, and rabbits with the three major isocyanates (TDI, MDI, HDI) have demonstrated that isocyanate skin exposure can induce systemic Th2-like sensitization and subsequent airway inflammation when followed by inhalation challenge (11)(12)(13)(14)(15). These studies have demonstrated that dose, route, and timing of the sensitizing dose are key determinants of sensitization and subsequent asthma.…”
Section: Animal Models Of Chemical and Protein Allergen Skin Exposurementioning
confidence: 99%